Kelsen on Democracy and Majority Decision - Eerik Lagerspetz (Franz Steiner Verlag, 2022)
This paper explicates some aspects of Hans Kelsen’s defence of democracy. Kelsen’s aim was to formulate a realistic normative alternative to the democratic ideal derived from Rousseau. He provided two, independent arguments for majoritarian democracy. First, the validity of majority principle could be derived from epistemological relativism. Second,  majority principle maximized individual liberty. The latter argument is based on Kelsen’s own definition of liberty as a correspondence between an individual will and the ruling norms. This argument could be interpreted as reasoning based on a hypothetical contract. The most important critiques of majoritarian proceduralism are based on (1) the problem of the possibility of democratic self-destruction, (2) the problem of the democratic origins of democracy and (3) the problem of the possibility  of permanent majorities. Kelsen had a convincing answer to problems, (1) and (2). The problem of permanent majorities is more difficult to solve.  Ultimately, Kelsen is forced to abandon his purely proceduralistic starting point.